Examining the relationship between athletes' achievement goal orientation and ability to employ imagery. (May 2016) - Gregg, Melanie J.; O, Jenny; Hall, Craig R.
Abstract: Objective: Imagery ability may be cognitively regulated by motivational states, thus it is important to determine the relationship between goal orientations and imagery ability. Design/Method: Participants were 272 male and female athletes, representing nine sports. Goal orientations and cognitive and motivational imagery abilities were assessed via questionnaires. Task and ego goal orientations were examined via a two-step cluster analysis procedure, resulting in the identification of four goal orientation clusters. Separate multivariate analyses were conducted to assess differences in cognitive imagery ability and motivational imagery ability for the clusters, with gender and sport type entered as covariates. Results: For cognitive imagery ability, gender had a significant effect for athletes with low task/low ego orientation; female athletes rated their internal imagery perspective as clearer and more vivid. Regarding motivational imagery ability, when sport type was controlled for, cluster membership demonstrated a significant multivariate effect. Goal orientations have a relationship with motivational imagery ability but this same relationship was not evident with cognitive imagery ability. Athletes with high task/high ego or high task/low ego goal orientations scored significantly higher on their ability to feel emotions and their ease of generating motivational general-mastery images compared to athletes with low task/high ego or low task/low ego orientations. No differences between goal orientation clusters were found for motivational general-arousal imagery ability. Conclusion: Athletes who have a high task orientation are very motivated and have an easy time forming mastery images and a high ability to experience the emotion of these images. Highlights: Athletes' task and ego goal orientations were examined via cluster analysis. Motivational imagery ability is cognitively regulated by motivational states. Goal orientations did not have a relationship with cognitive imagery ability. Athletes with high task orientation effectively experience the emotions of images.